Bioinspired aligned wrinkling dressings for monitoring joint motion and promoting joint wound healing. (13th July 2022) - Zhou, Xiaohui; Feng, Pingping; Liu, Huanliang; Song, Botao
Abstract : Bioinspired aligned wrinkling dressings are prepared for monitoring joint motion and promoting joint wound healing. Abstract : Joint skin wounds are difficult to treat because of the frequent large motion of these active wounds; thus, dressings capable of simultaneous real-time monitoring of joint motion and promoting joint wound healing are highly needed. Herein, inspired by the aligned wrinkling microstructure and sensing functions of normal joint skins, we combine the electrospinning technique with a water-induced self-assembly approach to prepare bioinspired conductive dressings with aligned wrinkles for achieving the above-mentioned bifunctions. The results indicate that both the wavelength and height of the bioinspired aligned wrinkles can be facilely tuned by adjusting the thickness ratio of the two layers and the loading amount of conductive microparticles. Owing to the unique aligned wrinkling structure and good conductivity, the bioinspired dressing can monitor the donor student's diverse joint motions. Interestingly, the dressing can also accurately monitor different types of mouse neck motion, including up/down and left/right movements. The in vivo wound repairing results confirm that the bioinspired dressing can accelerate the healing of active wounds on the mouse neck by promoting collagen deposition, hair follicle regeneration, and epithelialization. The bioinspired dressing with the integration of real-time motion monitoring features and wound repairing functions will open a new avenue to improve the management of joint wounds.